2002
DOI: 10.1051/0004-6361:20020170
|View full text |Cite
|
Sign up to set email alerts
|

The BeppoSAX view of bright Compton-thin Seyfert 2 galaxies

Abstract: Abstract. We present the analysis of 31 observations (17 of which are published here for the first time) of 20 bright Compton thin Seyfert 2 s, in the 0.1-200 keV band, performed with the BeppoSAX satellite. The sample consists of all Seyfert 2 s in the BeppoSAX public archive, with a 2-10 keV flux higher than 5 × 10 −12 erg cm −2 s −1 . The good statistics available and the broad energy band permit a detailed study of the main continuum components of these sources, i.e. the primary power-law, the reflected co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
145
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(179 citation statements)
references
References 28 publications
32
145
0
2
Order By: Relevance
“…The same result was obtained by Risaliti (2002), who studied Seyfert 2s with BeppoSAX and found that the cold reflection component is compatible with being non-variable. They argue that if the reflection originates in the accretion disk, the reflection and the transmitted components must be closely related, but if the distance of the reflector to the SMBH is greater than the light crossing time of the intrinsic variations, the reflected component must remain constant.…”
Section: Compton-thicknesssupporting
confidence: 83%
See 2 more Smart Citations
“…The same result was obtained by Risaliti (2002), who studied Seyfert 2s with BeppoSAX and found that the cold reflection component is compatible with being non-variable. They argue that if the reflection originates in the accretion disk, the reflection and the transmitted components must be closely related, but if the distance of the reflector to the SMBH is greater than the light crossing time of the intrinsic variations, the reflected component must remain constant.…”
Section: Compton-thicknesssupporting
confidence: 83%
“…They found short-term variations (hours) from the analysis of a light curve from 1996 and longterm variations when comparing the flux of these data with previous data from 1995, when it was about three times brighter. Risaliti (2002) studied two BeppoSAX observations taken in October 1996 and November 1997 and fit the data with an absorbed power law, a thermal component, a cold reflection, a warm reflection, and a narrow Gaussian line. They reported very similar spectral parameters for the two spectra.…”
Section: Appendix B: Notes and Comparisons With Previous Results For mentioning
confidence: 99%
See 1 more Smart Citation
“…In Compton-thick AGN, residual X-ray emission red-wards the photoelectric cutoff could be due to Compton-reflection of the otherwise invisible primary radiation off the obscuring matter 4 . Fe K α fluorescent emission with large EW ( ∼ > 600 eV, Risaliti 2002;Guainazzi et al 2005) is the unmistakable "smoking gun" of a Compton-thick AGN. We have therefore applied the baseline spectral model for Comptonthick AGN to the PKS1627+06 pn spectrum (the MOS spectra have very poor statistics, and do not provide any further constraints): a pure Compton-reflection continuum (model pexrav in Xspec, Magdziarz & Zdziarski 1995) plus a Gaussian unresolved emission line.…”
Section: A Compton-thick Agn In Pks1607+26?mentioning
confidence: 99%
“…A large region of this parameter space is virtually unexplored because we currently lack information on large AGN samples. Observations by BeppoSAX (Risaliti 2002;Perola et al 2002) of a handful of radio quiet sources, loosely locate this drop-off in the range 30- Figure 2. The 0.25-400 keV cosmic X-/γ−ray background spectrum fitted with synthesis models; measurements are from observations with different experiments as labelled.…”
Section: The Origin Of the Soft γ-Ray Backgroundmentioning
confidence: 79%